Holistic Approaches to Bullying Prevention: The Mediating Role of School Well-Being, Self-Management, and Empathy - Pusvitasari, Rita; Zarkasyi, Ahmad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research aims to examine the influence of self-management and empathy on the tendency of bullying behavior among teenage students through the mediating role of the school well-being variable for students in the three largest Islamic boarding schools in Jember Regency, East Survey Province. This research is a non-experimental quantitative research with a survey design. A total of 160 randomly selected students participated in this survey research. The data that has been collected is then analyzed using the WARP PLS 7 application and the IBM Statistical Package for Social Science (SPSS) version 23 application. The analysis results using WARP PLS 7. Found values that show that: 1) self-management influences the sixth tendency of bullying through school. Well-Being is 13.5%. This result means that the higher the student’s self-control, demonstrated by the ability to control their emotions when teased by friends, the better the social relations between students, teachers, and school employees, which will impact their behavior in avoiding the use of bad words. Put down friends you do not like. 2) empathy influences the tendency for bullying behavior through School Well Being by 23.8%. This result means that the higher the perspective shown by the attitude of trying to see a problem from another person’s point of view, the better the social relations between students and teachers and school employees so that it has an impact on behavior to avoid using bad words to demean friends who are not liked.